Study the effect of isothermal aging on Sn-Ag-Cu (SAC) lead-free solder added with silicon carbide (SiC)
The usage of composite solder is one of the method in improving stability of the solder joints. Addition of certain particles such SiC to form a composite solder has been given greater attention since it can enhance the mechanical properties of solder and has been proven by other researchers. This study was focus on the effect of isothermal aging on the contact angle, intermetallic compound (IMC) layer growth and mechanical properties of solder. In this study, Sn-3Ag-0.5Cu (SAC305) solder was used as based matrix and 0.75 wt% of SiC was added into tin silver copper (SAC) solder as reinforcement particles. The composite solder was prepared by using powder metallurgy method which consists of mixing, compacting and sintering. The characterization of lead-free solders, especially after isothermal aging, is very important in order to accurately predict the reliability of solder joints. This study was divided into two phases. Phase one is about the process of sample preparation and characterization studies of solder reliability before isothermal aging process for both SAC and SAC-SiC composite solder. The characterization divided into microstructural, physical, solderability and mechanical properties. Phase two is related to reliability of solder after isothermal aging process. In this phase, the reaction between solder and copper (Cu) substrate after aging was observed. Found that, the contact angle of SAC and SAC-SiC composite solder were increased with aging temperature and time. The contact angle of SAC-SiC composite was lower than SAC solder due to the segregation of SiC reinforcement particles along the wetting point. IMC layer thickness of solder was increased when the aging temperature and time was higher. The presence of SiC in SAC solder remain as stable solid particles during reflow process and retard the IMC growth for SAC-SiC composite solder. The SiC particles tend to stay preferentially on IMC layer and act as a barrier which helps to reduce the IMC layer growth by blocking the diffusion of Cu atoms from Cu substrate to the solder. The activation energy of SAC-SiC composite also becomes higher and caused the growth of IMC layer more difficult than SAC solder. As the aging temperature and time increased, the microhardness of solder was slightly decreased. The microhardness for SAC-SiC composite was higher than SAC solder due to the homogenous distribution of SiC and fine IMC particles including Cu6Sn5 and Ag3Sn when SiC was added into SAC solder. The shear strength of SAC and SAC-SiC composite solder were decreased when aging temperature and time increased. However, the shear strength value for SAC-SiC composite solder was consistently higher compared with SAC solder due to the presence of SiC which acts as obstacles for dislocation motion and leads to the increasing of shear strength. The fracture surface at the interface between SAC-SiC composite solder and Cu substrate exhibit the ductile fracture with rough dimple surface. Overall, the addition of SiC as reinforcement into SAC lead-free solder matrix has improved the contact angle, IMC layer growth and mechanical properties of the solder materials after isothermal aging process.